Strategic divide management in pharmaceutical alliances: A partner’s strategic evolution as a reason for strategic divide - Ostela, Saija (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Strategic alliances are widely used in the pharmaceutical industry and, ideally, they are long-lasting structures that bring many benefits and value to the alliance partners. However, organizations continuously encounter pressures to enhance performance, while the environment in which they operate evolves. Therefore, an alliance partner might be forced to change its strategy, which can lead to the partners’ misaligned priorities and strategic divide. The academic literature acknowledges the impact a partner’s strategic change can have on the value of the alliance, but the phenomenon is not studied further, which is why the purpose of this study is to understand the role that a partner’s strategic evolution plays in strategic alliances within the pharmaceutical industry. The main purpose is further divided into three sub-objectives: 1) Describe reasons behind the strategic direction change of a partner firm, 2) Understand the consequences of partners’ misaligned priorities, and 3) Describe proactive and reactive ways to manage strategic divide between alliance partners. Since the phenomenon is not studied much, the empirical part of the study was conducted as a qualitative analysis using expert interviews to better understand, how the partner’s strategic evolution affects the alliance. The empirical data was organized into themes, according to the researcher’s interpretations on the interviews. The research findings demonstrated, how the partners change their strategies if the external or organizational environments change. The strategic changes, again, cause strategic divides between the alliance partners that are likely to have an impact on the alliance value. The findings revealed that the interviewees consider anticipation of the partner’s strategic change to be really difficult, but, at the same time, it was noted that a proactive strategic divide management could help to prevent and detect some divides. Additionally, the results showed that, after the detection, a reactive approach in a controlled manner was seen to be the most beneficial for the alliance’s future performance. This study proved that a partner’s strategic evolution affects the partners’ priority alignment and alliance value, which is why the strategic divide management is important in organizations that are involved with strategic alliances. In order to understand the role of a partner’s strategic evolution and provide managers with a tool to manage alliances and strategic divides, the study combined the alliance lifecycle as well as the proactive and reactive approaches to strategic divide, and presented a framework for strategic divide management.